(untitled) (Research, Society and Development, 2022)
The aging process generates several changes, such as decreased balance and reduced muscle strength, which can cause falls that, as a consequence, lead to reduced functionality, thus compromising the functional capacity of the elderly. The objective of this review was to analyze the effects of the Pilates method on the functionality of the elderly. This is an integrative review study composed of 6 phases: creation of the guiding question, objective, inclusion and exclusion criteria, search in databases, analysis, categorization of studies, exposure and discussion of results. The search was performed in Medline, Lilacs via Virtual Health Library (VHL), National Library of Medicine (Pubmed) and Scopus and Physiotherapy Evidense Database (PEDro) databases, using the Descriptors in Science and Health Decs: Exercise movement techniques, Aged, Elderly health, combined with the boolean operator “AND”, the year of publications was between 2017 and 2022. With the application of the inclusion and exclusion criteria, 6 texts were obtained at the end. The studies functional analyzed the effects of the practice of the Pilates method on the health of the elderly, several effects observed were beneficial to improve the functional capacity and consequently the functionality of the elderly. phase a more active and healthy aging in the elderly.